Brachial Plexus Surgery - Sevline Estethia Ompusunggu; Rully Hanafi Dahlan (Indoscholar, 2018)
The magnitude problems of brachial plexus lesions are not only about the surgical approaches but also the basic problems. Its vague clinical symptoms, the complexity of anatomy structure, the use of advanced imaging followed by electrophysiology to address the lesions, and the challenging of surgical timing and options make those lesions management more challenging. These challenges in Indonesia are more difficult because not so many neurosurgeons are familiar with brachial plexus surgery. Brachial plexus surgery is in evolution. For brachial plexus nerve sheath tumours, a fascicular level resection of tumours and preservation of uninvolved fascicles is now possible. Neuropathic pain may be improved by a dorsal root entry zone lesion procedure. The timing of surgery is different in each pathology, especially in traumatic injury. In traumatic injury, it depends on several factors, e.g. the mechanism of injury, type of injury, the speed of the vehicle, and the mode of fall while victim lands on the ground. The common surgical options in traumatic injury are direct repair by means of an end-to-end suture, external neurolysis, nerve grafting, and nerve transfers. Secondary reconstruction to improve function has been widely introduced such as soft-tissue reconstruction (tendon/muscle transfer or free muscle transfer) and bone procedures (arthrodesis or osteotomy). Brachial plexus surgery demands a broad multidisciplinary approach to a common problem, targeting not only the peripheral nerve, but also the brain, spinal cord, muscle, end-organ, bone and joints, and their complex interactions.